Experimental Study on Seepage Properties of Jointed Rock-Like Samples Based on 3D Printing Techniques. (21st January 2020) - Tan, Wenhui; Wang, Pengfei
Abstract : Sample making of fractured rock mass is a big problem in rock mechanical test. The specimens prepared by traditional rock core drilling have some disadvantages such as unclear internal structure and great difference in mechanical properties; while, the samples prepared by inserting and seaming method have some other disadvantages such as hard to control the attitude of precast-joints, low accuracy. A method for preparing fractured rock-like samples based on 3D printing technology is introduced in this paper, and the seepage characteristics of fractured rock-like samples is studied by seepage experiments. Firstly, the standard profile curves of 10 grades of joint roughness are digitized and 10 groups of 3D digital fracture models are established with different roughness and thickness (i.e., 1.5, 3.0, and 5.0 mm, respectively). 30 fracture inserts are produced by 3D printing technology. Then, rock-like specimens with through-filling fractures are poured with molds. Finally, the permeability tests of the prepared rock-like specimens are carried out to study the seepage characteristics of fractures with different roughness and gap widths under different confining pressures. The results show that 3D printing technology provides an effective way for production of complex crack samples in laboratory test and the comparative analysis of tests. The seepage characteristics of fractures are well studied. When the gap width is small, the permeability decreases with the increase of roughness, and the influence of roughness on fracture permeability decreases rapidly with the increase of confining pressure and gap width. The permeability of through-filling fractures with different roughness and gap width decreases with the increase of confining pressure. The relationship between confining pressure and fracture permeability can be described by the power function. 3D printing technology overcomes the shortcomings of traditional specimen preparation methods and greatly improves the precision of crack inserts. The jointed rock-like model established by the method revealed the influence of fracture characteristics on seepage flow very well.